2014
DOI: 10.1080/09500782.2014.977294
|View full text |Cite
|
Sign up to set email alerts
|

Embracing plurality through oral language

Abstract: The transmission and dissemination of knowledge in Aboriginal societies for the most part occurs orally in an Aboriginal language or in Aboriginal English. However, whilst support is given to speaking skills in Indigenous communities, in our education system less emphasis is given to developing equivalent oral communicative competence in Standard Australian English (SAE). Instead the focus is given to the ongoing assessment of reading and writing skills and grammatical knowledge À this is in direct contrast to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 39 publications
(49 reference statements)
0
1
0
Order By: Relevance
“…Studies have found that the institutional use of the NAPLAN test as an accountability measure has led to greater tensions between the external curriculum demands and individual students’ learning needs (Dreher 2012), and accompanying changes in classroom practice in literacy teaching (Hardy 2013). Other studies have raised the issues of reliability of the NAPLAN test as a valid indicator of EAL (English as an additional language) and Aboriginal students’ achievements (Wigglesworth, Simpson & Loakes 2011; Angelo 2013; Dixon 2013; Freeman 2013; Nguyen, Oliver & Rochecouste 2015). Consistent with these studies, in a submission to the Senate Education, Employment and Workplace Relations Committee, the Australian Council of TESOL Associations (ACTA 2013) questioned the effectiveness of this standardized testing regime.…”
Section: Language Testing and Assessmentmentioning
confidence: 99%
“…Studies have found that the institutional use of the NAPLAN test as an accountability measure has led to greater tensions between the external curriculum demands and individual students’ learning needs (Dreher 2012), and accompanying changes in classroom practice in literacy teaching (Hardy 2013). Other studies have raised the issues of reliability of the NAPLAN test as a valid indicator of EAL (English as an additional language) and Aboriginal students’ achievements (Wigglesworth, Simpson & Loakes 2011; Angelo 2013; Dixon 2013; Freeman 2013; Nguyen, Oliver & Rochecouste 2015). Consistent with these studies, in a submission to the Senate Education, Employment and Workplace Relations Committee, the Australian Council of TESOL Associations (ACTA 2013) questioned the effectiveness of this standardized testing regime.…”
Section: Language Testing and Assessmentmentioning
confidence: 99%